Estudio de 2da generación de conejos en el trópico con el uso de suplementos vitamínicos, sobre los índices de rendimiento productivo y la madurez sexual. - Briones Bermeo, Edson Alivett (2024)
The objective of this research is to study the adaptation of rabbits in the tropics with the use of vitamin supplements on productive performance indices and biological behavior. The experiment was carried out in the Minor Species program of the Faculty of Agricultural Sciences of the Technical University of Babahoyo, for its development 36 weaned rabbits (35 days) of a New Zealand breed, Belier, Rex and Lion's Head were used randomly distributed in 3 groups that correspond to the T0 treatments (Alfalfa + Balanced + Water ad libitum); T1 (Alfalfa + Balanced + Water ad libitum with B Complex (2gr/L) and T2 (Alfalfa + Balanced + Water ad libitum with Vitamin C (15ml/L), diet they received daily for 12 weeks of study. For data analysis, used the Completely Randomized Design (DCA), where the experimental results obtained were subjected to an Analysis of Variance for the differences (ANDEVA), and Mean Separation according to Tukey at the significance levels of (P ≤ 0.05 and P ≤ 0.01) The results indicate that the best initial weight was in the Belier Breed group with the use of the vitamin (471.33g), in relation to the final weight the best was 7745.67g corresponding to the Belier group with the use of B complex. , while the highest weight gain was recorded in the Belier breed with 7350.00g, while the Rex breed recorded the best Cost Benefit with 4.81.